Makueni County Gender Transformative Socio-Technical Innovation Bundles (GTGSTIBs) scaling roadmap - Nyamolo, Victor; Lutomia, Cosmas; Njiru, Emerita; Muteti, Mary; Muema, Eunice; Ouya, Frederick; Waswa, Boaz; Nchanji, Eileen (Bioversity International and International Center for Tropical Agriculture, 2025)
This roadmap charts a strategic pathway for scaling gender-transformative socio-technical innovation bundles (GTGSTIBs) across Makueni County, building on successful pilot interventions implemented between 2022 and 2024 under the CGIAR Gender Equality initiative (HER+), Diversification in East and Southern Af rica (Ukama Ustawi), and Kenya Agricultural and Livestock Research Organization (KALRO). The roadmap emerged from stakeholder dialogues held on September 15th -16th, 2025, in Wote, Makueni county, bringing together county government departments, research institutions, extension officers, farmers, sub-county agricultural officers, ward agricultural officers, NGOs, and private sector actors. Makueni County faces persistent challenges in its maize-legume production systems, including gender inequality, climate vulnerability, inadequate extension services, and limited access to agricultural inputs. This roadmap outlines a comprehensive implementation framework anchored in the County Agriculture Sector Steering and Coordination Committee (CASSCOM), with five strategic pillars: extension integration, program and policy alignment, private-sector engagement, equity and inclusivity, and monitoring and institutionalisation. The approach emphasises phased implementation, multi-stakeholder coordination, and resource mobilisation strategies that leverage both public investment and private sector partnerships. Key targets include training additional Trainers of Trainers (ToTs) and Community Resource Persons (CORPs), integrating GSTIBs into the County Integrated Development Plan (CIDP) 2023-2027 and National Agricultural Value Chain Development Projects (NAVCDP), strengthening public-private partnerships for input supply and market linkages, and ensuring inclusive access for women, youth, and persons with disabilities. Success will require coordinated action, sustained political commitment, adequate resource allocation, and continuous learning and adaptation.